A study of household food security and adoption of biofortified crop varieties in Tanzania: the case of orange-fleshed sweetpotato - Okello, J.J.; Sindi, K.; Shikuku, Kelvin Mashisia; McEwan, M.; Low, Jan W. (IntechOpen, 2017)
Food insecurity has become a key issue in the field of development in recent years with major inadequate intake of vitamin A-rich foods. Specifically, vitamin A deficiency (VAD) remains a major health problem among poor developing-country households, especially in Africa. Efforts to combat VAD currently focuses on food-based approach that entails breeding for crops that are rich in beta carotene, a precursor for Vitamin A. Success has been registered in sweetpotato, cassava and maize. Among these crops, the greatest effort has gone into promoting the production and consumption of orange-fleshed sweetpotato (OFSP). These efforts include sensitization of farmers on the nutritional benefits of OFSP and the provision of clean sweetpotato planting materials. This study used a rich dataset collected from 732 farm households in Tanzania to assess of effect of household food insecurity and benefit awareness on the adoption of OFSP varieties. The study found that the household food security and awareness of the benefit of OFSP affect the decision to adopt OFSP varieties. It also found evidence that agroecology and farmer endowment with financial and physical assets affect the decision to grow OFSP varieties. It discusses lessons and policy implications of the findings for other countries.